Creating Safe and Supportive Environments: A Policy for Addressing Sexual Violence in Islamic Religious Universities - Nilawati Nilawati; Rr Rina Antasari; Erniwati Erniwati; Helen Sabera Adib; Dolla Sobari (STAI Hubbulwathan Duri, 2023)
The Ministry of Religion is committed to preventing and dealing with sexual violence by issuing a policy in the form of Director General's Decree Number 5494 of 2019 which applies to all Islamic Religious Universities. This research aims to determine the implementation of this decree and the factors that hinder it. The research method used is qualitative with an empirical juridical approach. Data collection methods use interviews and documentation. The informants for this research were 26 PTKIN/PTKIS randomly. The data analysis method uses descriptive analysis. This research found that the Director General's Decree Number 5494 of 2019 has not been implemented properly. The factors that influence this are 1) not all PTKI have regulations derived from the Director General's Decree Number 5494 of 2019; 2) the PTKI leadership's concern regarding the issue of sexual violence on campus is still weak; 3) there is still a legal culture in the campus community that prioritizes protecting the disgrace/dignity of higher education rather than the losses suffered by victims; 4) lack of human resources who understand gender mainstreaming and victim protection; and 5) lack of funding. Efforts that need to be made to create a campus free from sexual violence are 1) making clear regulations regarding the prevention and handling of sexual violence on campus; 2) strengthening the academic community's understanding of gender mainstreaming; and 3) forming an integrated service unit. Thus, the implementation of the decree has not been implemented well with various obstacles.